Quantitative Palynology Informing Conservation Ecology in the Bohemian/Bavarian Forests of Central Europe - Carter, Vachel A.; Chiverrell, Richard C.; Clear, Jennifer L.; Kuosmanen, Niina; Moravcová, Alice; Svoboda, Miroslav; Svobodová-Svitavská, Helena; van Leeuwen, Jacqueline F. N.; van der Knaap, Willem O.; Kuneš, Petr (Frontiers in Plant Science, 2018)
In 1927, the first pollen diagram was published from the Bohemian/Bavarian Forest region of Central Europe, providing one of the first qualitative views of the long-term vegetation development in the region. Since then significant methodological advances in quantitative approaches such as pollen influx and pollen-based vegetation models (e.g., Landscape Reconstruction Algorithm, LRA) have contributed to enhance our understanding of temporal and spatial ecology. These types of quantitative reconstructions are fundamental for conservation and restoration ecology because they provide long-term perspectives on ecosystem functioning. In the Bohemian/Bavarian Forests, forest managers have a goal to restore the original forest composition at mid-elevation forests, yet they rely on natural potential vegetation maps that do not take into account long-term vegetation dynamics. Here we reconstruct the Holocene history of forest composition and discuss the implications the LRA has for regional forest management and conservation. Two newly analysed pollen records from Prášilské jezero and Rachelsee were compared to 10 regional peat bogs/mires and two other regional lakes to reconstruct total land-cover abundance at both the regional- and local-scales. The results demonstrate that spruce has been the dominate canopy cover across the region for the past 9000 years at both high- (>900 m) and mid-elevations (>700-900 m) elevations. At the regional-scale, inferred from lake records, spruce has comprised an average of 50% of the total forest canopy; whereas at the more local-scale at mid-elevations, spruce formed 59%. Beech established 6000 cal yr BP while fir established 5500 cal yr BP, and reached a maximum land-cover abundance of 24% and 13% roughly 1000 years ago at mid-elevations. Over the past 500 years spruce has comprised 47% land-cover, while beech and fir comprised 8% and <5% at mid-elevations. This approach argues for the ‘natural’ development of spruce and fir locally in zones where the paleoecology indicates the persistence of these species for millennia. Contrasting local and regional reconstructions of forest canopy cover points to a patchwork mosaic with local variability in the dominant taxa. Incorporation of paleoecological data in dialogues about biodiversity and ecosystem management is an approach that has wider utility.